Review of advances and changes in cybersecurity in Peru, for a digital transformation - León Gutierrez, Edwin Daniel (2022)
This work aims to explore publications where the topic of cybersecurity in Peru has been treated. For this, 12 original articles have been reviewed about the subject, published in the last five years. This article has a clear, descriptive, exploratory objective.